THREE-DIMENSIONAL WEB-BASED PHYSICS SIMULATION APPLICATION FOR PHYSICS LEARNING TOOL - Salim, William; Setiawan, Arden Sagiterry; Purnama, Yudy (Bina Nusantara University, 2012)
The purpose of this research is to present a multimedia application for doing simulation in Physics. The application is a web based simulator that implementing HTML5, WebGL, and JavaScript. The objects and the environment will be in three dimensional views. This application is hoped will become the substitute for practicum activity. The current development is the application only covers Newtonian mechanics. Questionnaire and literature study is used as the data collecting method. While Waterfall Method used as the design method. The result is Three-DimensionalPhysics Simulator as online web application. Three-Dimensionaldesign and mentor-mentee relationship is the key features of this application. The conclusion made is Three-DimensionalPhysics Simulator already fulfilled in both design and functionality according to user. This application also helps them to understand Newtonian mechanics by simulation. Improvements are needed, because this application only covers Newtonian Mechanics. There is a lot possibility in the future that this simulation can also covers other Physics topic, such as optic, energy, or electricity.Keywords: Simulation, Physic, Learning Tool, HTML5, WebGL